Glucose-potassium ratio: a prognostic biomarker enhancing outcome prediction in mild-to-moderate traumatic brain injury - Wang, Jiayin; Hong, Chaocan; Feng, Qiangqiang; Wu, Baofang; Li, Shaojie; Yan, Changhu; Gao, Hongzhi (Frontiers in Neurology, 2025)
BackgroundTo determine the prognostic value of the serum glucose-to-potassium ratio (GPR) in patients with mild-to-moderate traumatic brain injury (MM-TBI).MethodsClinical data from patients admitted to the Second Affiliated Hospital of Fujian Medical University with MM-TBI between January 1, 2018 and December 31, 2022 were analyzed. Univariate logistic regression was performed to identify potential risk factors for poor prognosis, followed by multivariate logistic regression to evaluate the Rotterdam score and GPR as independent prognostic factors. The stability of the relationship between GPR and prognosis was confirmed using trend tests, multiple regression models, and restricted cubic splines (RCS). Propensity score matching (PSM) was used to adjust for selection bias, receiver operating characteristic (ROC) curves were used to evaluate predictive accuracy, and Kaplan–Meier (K-M) curves were used to assess 90-day prognosis.ResultsGPR (p = 0.0021) and Rotterdam score (p < 0.0001) were found to be independent prognostic factors. Trend tests and RCS analyses confirmed a stable, nonlinear relationship between GPR and prognosis. The area under the ROC curve was 0.670 for GPR alone, which increased to 0.850 when combined with the Rotterdam score. PSM analysis revealed a significant difference in GPR between the favorable and unfavorable prognosis groups (p = 0.004). K–M curves showed that GPR was strongly predictive of 90-day outcomes (p < 0.0001).ConclusionGPR is a reliable and easily accessible prognostic indicator for MM-TBI. Moreover, its prognostic value is enhanced when GPR is combined with the Rotterdam score.